Compliant contact force models in multibody dynamics : evolution of the Hertz contact theory - Machado, Margarida F. (2012)
Over the last decades, several compliant contact force models have been proposed. However, no complete and systematic comparison has been done on these models, which provides information on their range of application and accuracy for use in different contact scenarios. Thus, the selection of an appropriate model for a given contact problem is still an important and challenging issue to be addressed. The Hertzian contact theory remains the foundation for almost all of the available force models, but by itself, it is not appropriate for most impacts in practice, due to the amount of energy dissipated during the impact. A good number of contact force models have been offered that augment the Hertzian law with a damping term to accommodate the energy loss during the impact process for small or moderate impact velocities. In this work, the main issues associated with the most common compliant contact force models of this type are analyzed. Results in terms of the dynamic simulations of multibody systems are presented, which allow for the comparison of the similarities and differences among the models considered.